Study on the survival rate of foreign direct investments in the countries of the Visegrad Group using event history analysis - Salamaga, Marcin (Publishing House of Wroclaw University of Economics and Business, 2023)
Foreign direct investment (FDI) is a process that starts at a point in time and may end over time or continue uninterrupted throughout the observation period. Certain economic conditions may incline investors to divest by liquidating a business entity or selling their shares in the company in which the FDIs were made. Therefore, this is an analogy with the occurrence of censored cases, which allows for the use of survival analysis tools in the examination of the duration of FDIs. The aim of this article was to compare the patterns of ‘survival’ of foreign direct investments in individual Visegrad Group countries based on the relevant tables showing ‘the duration of FDIs’ and the survival curves obtained using the Kaplan-Meier estimator according to the criteria of sector and country of origin of the foreign capital. The Cox proportional hazards model was used to model the risk of foreign divestment. Based on the results obtained, the rate of decline in the cumulative probability of FDI survival shows differences between countries; FDI survival medians also vary across countries. In particular, it is demonstrated that the highest probability of foreign direct divestment in Poland applies to projects which are approximately 13.5 to 15 years long. In Czechia, this concerns projects which are approximately 18 to 21 years old, while in Slovakia and Hungary it is projects which are longer than 21. The study also shows that in all Visegrad countries, FDIs with German capital lasted the shortest, while projects with French capital lasted the longest (in the Czech Republic, Poland, and Hungary). In the majority of the Visegrad Group countries, the highest risk of divestment is typical of projects in sectors other than industrial processing and financial, insurance and other services. The data for the computations are from the Orbis and Zephir databases.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 83-99
Keywords: FDI; survival analysis; Visegrad Group